Fluctuating asymmetry of leave’s silver birch (Betula pendula Roth) (Ecological Bulletin of Kryvyi Rih District, 2019)
The variability of morphological parameters of the silver birch’s leaf blade (Betula pendula Roth.) was investigated in diﬀerent parks and gardens plant community in Kamianske city (Dnipropetrovsk region, Ukraine). The current level of ﬂuctuating asymmetry (FA) as an integral indicator of the test plant condition in diﬀerent ecological conditions of this industrial city was analyzed. It was found out that the ﬂuctuating asymmetry value (FA =0.054) induces the maximum permissible level of anthropogenic inﬂuence at the birch silver in the most distant from industrial enterprises (residential block «Romankovo») area. The values of the ﬂuctuating asymmetry that were installed on other sites («Center» — FA = 0;055 and «Station» — FA = 0.063), manifest extremely unfavorable environmental conditions (test plants are in a very depressed state).
Keywords: Betula pendula; biometry of leaf blade; ﬂuctuating asymmetry; bioindication; Kamianske city